Quality of Life and Well-Being in an Indian Ethnic Community The Case of Badagas - Davey, Gareth (SpringerBriefs in Well-Being and Quality of Life Research, 2018)
This book explores the quality of life of Badagas, an ethnic minority group in South India, as they navigate a society in flux, with specific reference to rural-to-urban migration and new media. At an empirical level, it reveals how Badagas understand themselves and the multifaceted changes in their culture and daily lives, exploring a pertinent concern at the forefront of debate about the future from a global perspective. The book draws attention to the fact that people are adopting flexible identities and lifestyles in an attempt to survive and thrive in a changing India and world, a new 'Indian-ness' shaped at the local level. It offers a timely update on previous research on Badagas, which dates to the 1990s, and also serves as an important case study on people's experiences of the social and economic transformation of Indian society as they become accustomed to new ideas, products, and ways of life. As such, it is a must-read for all those interested in quality of life in India and developing societies. .